Kompetensi Manajerial Kepala Sekolah dalam Pelaksanaan Ujian Nasional Berbasis Komputer di Kabupaten Banyuasin - Rusmawati Rusmawati; Ermis Suryana; Edi Harapan (Studia Manageria, 1970)
This study aims to analyze the Principal managerial competence in the management of teachers and staff, students, and management of UNBK facilities and infrastructure in planning, organizing, implementing, and evaluating in implementing the 2018 UNBK at SMAN 1 Talang Kelapa, SMA Plus Negeri 2 Banyuasin 3, and Banyuasin SMAN 1 1. This study uses instruments collecting data in the form of: interview, documentation, and observation. The sources of the data research were principals, vice principals, heads ofcomputer laboratories, heads of administration, and teachers at the school. The results of this study illustrate the principal managerial competence in: 1) planning the UNBK from the implementation of socialization, establishing committee members and committee meetings for additional hours of study and try out, and provision UNBK facilities and infrastructure, 2) organizing the implementation of UNBK through the establishment of committee, supervisors, and the UNBK implementation team accompanied by the issuance of the principal's decree and subrayon, 3) implementing the UNBK through the coordinating of UNBK teachers and implementing staff, procurement, management and maintenance of UNBK facilities and infrastructure, and 4) evaluating the implementation ofUNBK through informal supervision using the interview method, participant observation, and documentation. From the whole activities that carried out as the implementation of the managerial competence, it can be stated that the principal managerial competence in implementing UNBK is well implemented so that UNBK can be carried out smoothly and successfully